Comprehensive characterization of motor and coordination functions in three adolescent wild-type mouse strains - Eltokhi, Ahmed; Kurpiers, Barbara; Pitzer, Claudia (Scientific reports, 2021)
Neuropsychiatric disorders are often associated with motor and coordination abnormalities that have important implications on the etiology, pathophysiology, and management of these disorders. Although the onset of many neuropsychiatric disorders including autism spectrum disorder, schizophrenia, and attention-deficit hyperactivity disorder emerges mainly during infancy and adolescence, most of the behavioral studies in mice modeling neuropsychiatric phenotypes are performed in adult animals, possibly missing valuable phenotypic information related to the effect of synaptic maturation during development. Here, we examined which behavioral tests assessing both motor and coordination functions can be performed in mice at two different adolescent stages. As strain and sex affect mouse behavior, our experiments covered both male and female mice of three inbred wild-type strains, C57BL/6N, DBA/2, and FVB/N. Adolescent mice of both postnatal days (P)22-30 and P32-40 developmental stages were capable of mastering common motor and coordination tests. However, results differed significantly between strains and sexes. Moreover, the 10-day interval between the two tested cohorts uncovered a strong difference in the behavioral results, confirming the significant impact of maturation on behavioral patterns. Interestingly, the results of distinct behavioral experiments were directly correlated with the weight of mice, which may explain the lack of reproducibility of some behavioral results in genetically-modified mice. Our study paves the way for better reproducibility of behavioral tests by addressing the effect of the developmental stage, strain, sex, and weight of mice on achieving the face validity of neuropsychiatric disorder-associated motor dysfunctions.